140k views
2 votes
Simplify 12x⁵y² ÷ 3x²y​

1 Answer

3 votes

Answer:

f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)f(x) = x2 – p(x + 1) – c, then (α + 1)(β + 1)

Explanation:

User Yaroslav Shabalin
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.